Low birth weight and its determinants in a teaching hospital of Karnataka, India - M., Sumana; Y., Sreelatha C.; S., Girija B.; M., Sundar; Gowda, Darshan (International Journal Of Community Medicine And Public Health, 2017)
Background: Low birth weight is prospective marker of future growth and development of children and retrospective marker of mother’s nutritional and health status. The low birth weight is considered as sensitive index of nation’s health and development. The low birth weight babies are at 20 time’s greater risk of dying than normal birth weight babies. Lower the birth weight, lower the chances of survival. Objectives of the study was to find out the proportion of low birth weight babies delivered in Sri Chamarajendra district hospital, Hassan, India and to describe the influence of some maternal and socio demographic factors on the birth weight of baby. Methods:A cross sectional, hospital based study was designed in post natal care wards of Sri Chamarajendra district hospital, Hassan, India from February 2012 to June 2012. 630 post natal mothers were selected for the study based on sample size estimation. Post natal mothers who delivered single, live babies were included and babies with congenital malformations and twins were excluded from the study. Results: A number of factors like teenage pregnancy and mothers age above 30 years, illiteracy of the mothers, lower socioeconomic status, short birth spacing, lack of antenatal care, inadequate consumption of IFA tablets, anemia during pregnancy, improper dietary intake, tobacco consumption, bad obstetric history, obstetric complications during the present pregnancy were found to be significantly associated with low birth weight. Conclusions:Most of the determinants of low birth weight can be managed easily by providing adequate antenatal care.